2020
DOI: 10.17161/kjm.vol13.13861
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette Use and Risk Behaviors among Lesbian, Gay, Bisexual, and Transgender Adults: The Behavioral Risk Factor Surveillance System (BRFSS) Survey

Abstract: Introduction: We studied prevalence of e-cigarette use among lesbian, gay, bisexual, and transgender (LGBT) individuals and its association with risk behaviors. Methods: Using data from the Behavioral Risk Factor Surveillance System (BRFSS) survey, we assessed self-reported sexual orientation, e-cigarette use, cigarettes, marijuana, smokeless tobacco, and high-risk behavior (using non-prescribed drugs, treatment for sexually transmitted disease, or receiving monetary or drug compensation in exchange for sex in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…After the start of the COVID-19 pandemic, SGM respondents’ mental and physical health worsened, and was significantly worse than respondents in the non-SGM group, although this difference could also reflect other time-related changes beyond the pandemic. Current research shows that the SGM population has a higher rate of tobacco use, which has been proposed as contributing to this increased prevalence ( Hoffman et al, 2018 , Al Rifai et al, 2020 , Morgan et al, 2020 ). However, our study identified differences between SGM and non-SGM respondents that are not explained by tobacco use, suggesting other social determinants of health impact these disparities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the start of the COVID-19 pandemic, SGM respondents’ mental and physical health worsened, and was significantly worse than respondents in the non-SGM group, although this difference could also reflect other time-related changes beyond the pandemic. Current research shows that the SGM population has a higher rate of tobacco use, which has been proposed as contributing to this increased prevalence ( Hoffman et al, 2018 , Al Rifai et al, 2020 , Morgan et al, 2020 ). However, our study identified differences between SGM and non-SGM respondents that are not explained by tobacco use, suggesting other social determinants of health impact these disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed explanations for these disparities lie in social determinants of health: social stressors, health disparities, socioeconomic marginalization, stigma, and minority stress ( Alzahrani et al, 2019 , Downing and Przedworski, 2018 , Al Rifai et al, 2020 , Fredriksen-Goldsen et al, 2013 ). Few studies additionally considered health access (for an exception, see Trinh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lesbian and gay adults had statistically significantly higher odds of being a current smoker and an everyday smoker than straight adults 10 . The prevalence of current e-cigarette use followed similar patterns 11 . Furthermore, sexual minority adults report a higher prevalence and higher severity of DSM-5 tobacco use disorder than straight adults 7 .…”
Section: Introductionmentioning
confidence: 76%
“…In 2014–2017 Behavioral Risk Factor Surveillance System, lesbian/gay and bisexual adults had significantly higher odds of reporting everyday smoking and current smoking (everyday or some days) compared to straight adults [ 12 ]. The prevalence of current e-cigarette use was most prevalent among US sexual minority adults [ 8 , 10 , 13 ]. Data from the 2016 Behavioral Risk Factor Surveillance System reported among data from 198,057 adults in 26 states that lesbian, gay, and bisexual adults were significantly more likely to ever and currently smoke cigarettes and e-cigarettes compared to straight adults [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from the 2016 Behavioral Risk Factor Surveillance System reported among data from 198,057 adults in 26 states that lesbian, gay, and bisexual adults were significantly more likely to ever and currently smoke cigarettes and e-cigarettes compared to straight adults [ 8 ]. Data from the US Behavioral Risk Factor Surveillance System in 2016, 2017, and 2018 ( n = 1,348,091) reported the prevalence of e-cigarette use among lesbian, gay, bisexual, or transgender (LGBT) adults was 13%, nearly twice that of straight adults (5%) [ 13 ]. In the Population Assessment of Tobacco and Health in 2013–2014, lesbian/gay and bisexual women had higher odds of regular use of cigarettes and e-cigarettes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%